Consideraciones para desarrollar una estrategia de fidelidad - Mauricio Vásquez, Katia (2014)
The article intends to develop a loyalty strategy. That  means having several loyal customers in order to continue leading the market for satisfying the needs, expectations and the commitment of the company. Current consumers are more demanding and ask for better quality and better products and services. According to Henry Assael (1998), being aware of theconsumer’s psychographic, demographic, behavioral and geographic characteristics is necessary in order to design the strategy. The proposal also includes designing the different formsof communication, taking into account the pertinent legislation, and mainly following the ethical code and not presenting deceitful advertising, and considering the new virtual media